2016
DOI: 10.1186/s12904-016-0138-z
|View full text |Cite|
|
Sign up to set email alerts
|

Community-based pediatric palliative care for health related quality of life, hospital utilization and costs lessons learned from a pilot study

Abstract: BackgroundChildren with chronic complex-medical conditions comprise a small minority of children who require substantial healthcare with major implications for hospital utilization and costs in pediatrics. Community-Based Pediatric Palliative Care (CBPPC) provides a holistic approach to patient care that can improve their quality of life and lead to reduced costs of hospital care. This study's purpose was to analyze and report unpublished evaluation study results from 2007 that demonstrate the potential for CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 35 publications
0
41
0
2
Order By: Relevance
“… 4 Many children with complex medical conditions remain in the hospital away from their families, although home health care is clearly cost effective as compared with inpatient medical management. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“… 4 Many children with complex medical conditions remain in the hospital away from their families, although home health care is clearly cost effective as compared with inpatient medical management. 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…This coordination between specialists and primary health services can be found in community-based PPC such as reported by Kaye et al [ 16 ]. According to Goldhagen et al this model was even found to improve health-related quality of life and to reduce hospitalisation utilisation and costs [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four articles included in the sample were published in 2014 10,18,19,21 , two in 2015 13,17 , five in 2016 15,16,20,22,23 , two in 2017 12,14 and one in 2018 11 . All studies were produced outside Brazil.…”
Section: Data Characterizationmentioning
confidence: 99%